Thyroid cancer: a case of parapharyngeal extension - Amir, Momina; Shahzaib Asif; Rabbya Naseem; Khalid, Shayan; Muhammad Faisal; Raza Hussain (Journal of the Pakistan Medical Association, 2025)
Thyroid cancer is frequently encountered in clinical settings. However, its metastasis to the parapharyngeal space is exceedingly uncommon, comprising only 0 to 5 % of head and neck neoplasms This case report highlights the extension of papillary thyroid cancer to the parapharyngeal space, its treatment, and outcome. If a mass is observed in the parapharyngeal region on imaging, clinicians should contemplate the likelihood of thyroid cancer and rule it out as a potential diagnosis. Keywords: Thyroid gland; Parapharyngeal space; Mandibulotomy.